Iron Deficiency Prolongs Seed Dormancy in Arabidopsis Plants - Murgia, Irene; Morandini, Piero (Frontiers in Plant Science, 2017)
The understanding of seed dormancy, germination and longevity are important goals in plant biology, with relevant applications for agriculture, food industry and also human nutrition. Reactive Oxygen Species (ROS) are key molecules involved in the release of dormancy, when their concentrations fall within the so called ‘oxidative window’. The mechanisms of ROS distribution and sensing in seeds, from dormant to germinating ones, still need elucidation. Also, the impact of iron (Fe) deficiency on seed dormancy is still unexplored; this is surprising, given the known pro-oxidant role of Fe when in a free form. We provide evidence of a link between plant Fe nutrition and dormancy of progeny seeds by using different Arabidopsis ecotypes and mutants with different dormancy strengths grown in control soil or under severe Fe deficiency. The latter condition extends the dormancy in several genotypes. The focus on the mechanisms involved in the Fe deficiency-dependent alteration of dormancy and longevity promises to be a key issue in seed (redox) biology.